(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Purpose: The purpose of the paper is to investigate the status of infrastructure investment deficit situation among BRICS nations and make an attempt to establish bonds as a source of financing infrastructure and analyze bonds being traded in the Capital market in India. Design/Approach: The research employs a quantitative method, Trend Analysis. Infrastructure investment deficit data were obtained from Global Infrastructure Outlook, Gross domestic savings rate data were collected from the World Bank database, Bonds maturity and corresponding yields were obtained from investing.com, Bonds traded in the capital market were accessed from NSE website. Findings: The study finds that infrastructure investment deficit is rising in BRICS nations and at the global level, the Gross domestic savings rate is high which can be channelized to suffice the infrastructure investment deficit status. The average yield of bonds being traded in BRICS nations is much higher than the yield of other major economies. From the analysis of Bonds traded in capital market (India), we observe that only those bonds are traded which have investment-grade credit Rating.